Habilidades sociales y funciones ejecutivas en un niño con TEA - Yaguachi Cárdenas, Cynthia Julasy; Almeida Muñoz, Ashley Lizbeth (Machala: Universidad Técnica de Machala, 2024)
The investigation of social skills and executive functions is crucial because over time these competencies become fundamental in educational environments, in such a way that obstacles may arise in student interactions, behavior, lack of attention and alterations in school coexistence, these alterations and limitations are related to neurodevelopmental pathologies such as ADHD, behavioral disorders and ASD. Therefore, what are the social skills and executive functions in a child with ASD With the objective of Analyzing the social skills and executive functions in a child with ASD; and with specific objectives of Describing the social skills in a child with ASD, and Evaluating the executive functions of a child with ASD. For the development of this research the qualitative paradigm has been used, which arises from the need to solve a problem. Applied tests: Social Skills Scale and the Battery of Neuropsychological Assessment for Executive Function in Children (ENFEN) by its acronym in Spanish. Results: Difficulties in communication, emotional expression and social skills are evidenced. The lack of eye contact, limitation in conversation topics and absence of non-verbal language suggest barriers in social interaction. In addition the lack of empathy, tendency to be direct and educational complications confirm patterns associated with Autism Spectrum Disorder. Limitations in emotional expression and understanding are revealed, as well as difficulties in stopping and reflecting before acting, emphasizing affectations in emotional regulation, sustained attention, decision making and planning. Suggesting a detailed evaluation and possible psycho-pedagogical interventions to improve the student's skills.
La investigación de las habilidades sociales y funciones ejecutivas es crucial debido a que estas competencias se vuelven fundamentales en entornos educativos, de tal manera que pueden surgir obstáculos en las interacciones estudiantiles, conducta, falta de atención y alteraciones en la convivencia escolar, estas alteraciones y limitaciones están relacionadas con patologías del neurodesarrollo como TDAH, trastornos de conducta y TEA. Por lo tanto Cuáles son las habilidades sociales y funciones ejecutivas en un niño con TEA Con el objetivo de Analizar las habilidades sociales y funciones ejecutivas en un niño con TEA; y objetivos específicos de describir las habilidades sociales en un niño con TEA; y evaluar las funciones ejecutivas de un niño con TEA. Para el desarrollo de esta investigación se ha utilizado el paradigma cualitativo, el cual surge de la necesidad de solucionar un problema. Test aplicados: Escala de Habilidades Sociales y batería ENFEN. Resultados: Se evidencian dificultades en la comunicación, expresión emocional y habilidades sociales. La falta de contacto visual, limitación en temas de conversación y ausencia de lenguaje no verbal sugieren barreras en la interacción social. Además, la carencia de empatía, la tendencia a ser directo y las complicaciones educativas confirman patrones asociados al Trastorno del Espectro Autista. Se revelan limitaciones en expresión y comprensión emocional, así como dificultades para detenerse y reflexionar antes de actuar, destacando afectaciones en regulación emocional, atención sostenida, toma de decisiones y planificación. Sugiriendo una evaluación detallada y posibles intervenciones psicopedagógicas para mejorar las habilidades del estudiante.
Keywords: HABILIDAD SOCIAL; FUNCION EJECUTIVA; AUTISMO; MENTE